Cardiovascular Risk Factors Among First-Degree Relatives of Patients with Premature Cardiovascular Disease in Malta. Baseline Findings from the CRISO Project - Mifsud JL; Galea J (Vascular Health and Risk Management, 2024)
Justin Lee Mifsud,1,2 Joseph Galea2 1Department of Nursing, Faculty of Health Sciences, University of Malta, Msida, Malta; 2Department of Medicine, Faculty of Medicine and Surgery, University of Malta, Msida, MaltaCorrespondence: Justin Lee Mifsud, Department of Nursing, Faculty of Health Sciences, University of Malta, Msida, Malta, Tel +35623401109, Email justin-lee.mifsud@um.edu.mtPurpose: A family history of premature atherosclerotic cardiovascular disease (ASCVD) confers a greater risk of developing ASCVD. However, the prevalence of ASCVD risk factors among asymptomatic Maltese adults with parental or fraternal history of premature ASCVD is unknown. The study aimed to evaluate and compare their risk with the general population.Patients and Methods: Posters to market the project were distributed in cardiac rehabilitation areas. Patients with premature cardiovascular disease facilitated recruitment by informing their relatives about the project. Medical doctors and cardiac rehabilitation nurses referred first-degree relatives. Posters were put up in community pharmacies, and an explanatory video clip was shared on social media for interested individuals to contact researchers. Those eligible were enrolled in a preventive cardiology lifestyle intervention. Their data were compared with the risk in the general population.Results: Many first-degree relatives had a suboptimal risk profile, with 60% (N = 89) having a total cholesterol level of > 5.0 mmol/L; 54% having a low-density lipoprotein-cholesterol level of > 3 mmol/L; 70.5% being overweight/obese, with 62% having a waist circumference greater than the recommended values; 34.8% having hypertension; 56.2% being inadequately adherent to the Mediterranean diet; 62% being underactive, with 18% being sedentary; and 25.8% being smokers. First-degree relatives had significantly higher proportions of underactive lifestyle (p = 0.00016), high body mass index (> 25kg/m2) (p = 0.006), and systolic blood pressure (p = 0.001) than the general population, with 30% having metabolic syndrome.Conclusion: This study determined the prevalence of lifestyle, biochemical, physiological, and anthropometric cardiovascular risk factors among asymptomatic first-degree relatives of Maltese patients with premature ASCVD. First-degree relatives had considerable prevalences of an underactive lifestyle, hypertension, and obesity, suggesting better screening and early risk factor intervention are needed to modify their risk of ASCVD.Plain Language Summary: This study was done to evaluate factors that can increase the risk of heart disease in siblings and offspring of Maltese patients who developed atherosclerotic cardiovascular disease (ASCVD) at a young age. Relatives were invited to meetings during which a risk evaluation was performed. The researchers found that relatives had a high prevalence of cardiometabolic risk factors, meaning they were at increased risk of developing the disease.The researchers have concluded that reducing the risk of ASCVD in individuals at increased risk requires developing and testing potentially sustainable risk factor modification strategies.Keywords: primary prevention, risk assessment, family history